Combating Youth Unemployment with a Fair EU Youth Guarantee - Dennis Tamesberger; Johann Bacher (CESifo Forum, 2021)
The Covid-19 pandemic and the accompanying policy measures implemented by governments worldwide in order to contain the spread of the coronavirus have strongly affected labor markets. As a consequence, most countries experienced sharp increases in unemployment rates especially at the onset of the pandemic. In many countries, the increase in unemployment was due to a reduction in hiring, thus affecting young job seekers. In this issue of CESifo Forum we provide deeper insights into the labor market effects of the crisis looking at various European countries, the US and Australia over the course of the pandemic. The authors find that young people were hit particularly hard. Furthermore, they analyze and propose policies mitigating these negative effects.
Keywords: 330